AKUNTANSI PERSEDIAAN PADA PT. LINTAS BATAS DAGANG INTERNASIONAL - Iis Prihartini; Featy Octaviany (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to determine the implementation of inventory accounting at PT. Lintas Batas Dagang Internasional period and to evaluate its compliance with applicable accounting standards. The research method used is a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The analysis focuses on inventory recording and inventory valuation. The results indicate that PT. Lintas Batas Dagang Internasional has implemented a fairly effective inventory accounting system in supporting the company’s operational activities. The inventory valuation method applied assists the company in determining ending inventory value and cost of goods sold more efficiently. However, several obstacles were still found in inventory administration management, requiring improved supervision and accuracy in recording to produce more accurate and efficient inventory information.